Comparison of Mental Toughness Between Athletes in Individual and Team Sports of the CISM of the I.R.I. - Abasgholipour , Amir (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: The objective of this study was to compare the levels of mental toughness among athletes from different sports within the national military teams of the Islamic Republic of Iran, focusing on both individual and team sports. Methods and Materials: This descriptive-applied study employed a causal-comparative (ex post facto) design. The sample consisted of 40 athletes from various sports, including volleyball, taekwondo, wrestling, pentathlon, and athletics. Participants were selected purposefully and completed the Sports Mental Toughness Questionnaire (SMTQ). Data were analyzed using one-way analysis of variance (ANOVA) to compare overall mental toughness and its subscales across different sports. Tukey’s post-hoc test was employed to identify specific group differences where significant ANOVA results were found. The assumptions for ANOVA, including normality, homogeneity of variances, and independence, were checked and confirmed. Findings: The one-way ANOVA revealed significant differences in overall mental toughness among the different sports (F(4, 39) = 27.02, p = 0.001). Significant differences were also found in the subscales of confidence (F(4, 39) = 20.52, p = 0.000), constancy (F(4, 39) = 17.54, p = 0.000), and control (F(4, 39) = 6.43, p = 0.001). Tukey’s post-hoc test indicated that taekwondo and volleyball athletes exhibited significantly higher mental toughness scores compared to athletes from wrestling, athletics, and pentathlon. Conclusion: The study concludes that the nature of the sport, particularly the level of physical and psychological demands, significantly influences mental toughness levels in athletes. Taekwondo and volleyball athletes displayed higher mental toughness, suggesting the need for sport-specific mental training programs. These findings highlight the importance of tailored psychological interventions to enhance mental toughness, particularly in competitive military sports environments.